Network dynamics engaged in the modulation of motor behavior in stroke patients - Pool, Eva‐Maria; Leimbach, Martha; Binder, Ellen; Nettekoven, Charlotte; Eickhoff, Simon B.; Fink, Gereon R.; Grefkes, Christian (Human brain mapping, 2018)
Stroke patients with motor deficits typically feature enhanced neural activity in several cortical areas when moving their affected hand. However, also healthy subjects may show higher levels of neural activity in tasks with higher motor demands. Therefore, the question arises to what extent stroke‐related overactivity reflects performance‐level‐associated recruitment of neural resources rather than stroke‐induced neural reorganization. We here investigated which areas in the lesioned brain enable the flexible adaption to varying motor demands compared to healthy subjects. Accordingly, eleven well‐recovered left‐hemispheric chronic stroke patients were scanned using functional magnetic resonance imaging. Motor system activity was assessed for fist closures at increasing movement frequencies performed with the affected/right or unaffected/left hand. In patients, an increasing movement rate of the affected hand was associated with stronger neural activity in ipsilesional/left primary motor cortex (M1) but unlike in healthy controls also in contralesional/right dorsolateral premotor cortex (PMd) and contralesional/right superior parietal lobule (SPL). Connectivity analyses using dynamic causal modeling revealed stronger coupling of right SPL onto affected/left M1 in patients but not in controls when moving the affected/right hand independent of the movement speed. Furthermore, coupling of right SPL was positively coupled with the “active” ipsilesional/left M1 when stroke patients moved their affected/right hand with increasing movement frequency. In summary, these findings are compatible with a supportive role of right SPL with respect to motor function of the paretic hand in the reorganized brain.